1979
DOI: 10.5271/sjweh.2649
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of chromosome aberrations in workers exposed to styrene.

Abstract: Increased frequency of chromosome aberrations in workers exposed to styrene. Scand. j. work environ. & health 5 (1979) 333-335. Chromosomal aberrations in lymphocytes from peripheral blood were significantly more frequent in six workers from a plant manufacturing polyester resin boats (average 10.8 per 100 cells) than in six age-and sex-matched referents (5.2 per 100 cells). The contamination of the workroom air with styrene, as measured on three occasions within three years in different areas of the plant, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Third, all defects were investigated with respect to selected characteristics of a waste site (e.g., sites with off-site migration of chemicals), to clarify whether these features increased the waste site's potential health risk. Finally, specific chemical groups associated with particular organ system defects in the literature were evaluated: pesticides associated with clefts (13)(14)(15) or musculoskeletal defects (16,17), metals associated with nervous system defects (18)(19)(20), solvents associated with nervous system defects (21-23) or digestive system defects (24,25), and plastics associated with chromosomal anomalies (26)(27)(28)(29).…”
Section: Abnormalities; Hazardous Waste; Registriesmentioning
confidence: 99%
“…Third, all defects were investigated with respect to selected characteristics of a waste site (e.g., sites with off-site migration of chemicals), to clarify whether these features increased the waste site's potential health risk. Finally, specific chemical groups associated with particular organ system defects in the literature were evaluated: pesticides associated with clefts (13)(14)(15) or musculoskeletal defects (16,17), metals associated with nervous system defects (18)(19)(20), solvents associated with nervous system defects (21-23) or digestive system defects (24,25), and plastics associated with chromosomal anomalies (26)(27)(28)(29).…”
Section: Abnormalities; Hazardous Waste; Registriesmentioning
confidence: 99%
“…Moreover, increased rates of chromosom e aberrat ion s have been found in wo rkers exposed to styrene (3,8). On the other hand, animal tests of carcinogenicity have been inconclusive (5).…”
mentioning
confidence: 99%
“…studies on workers occupationally exposed to styrene have shown increased frequencies of chromosome damage at exposure levels of 25-300 ppm as the 8-h time-weighted average (1,3,4,7). In Sweden the exposure levels have decreased considerably during the last few years.…”
mentioning
confidence: 99%